Governance and Financing of Chinese Higher Education - Wang, Chengzhi (Education Policy Analysis Archives, 2000)
With an introduction to the overall underdevelopment of higher education in China compared with the American counterpart, this article briefly examines the main trends of over two decades of development of the governance and financing systems of China's higher education sector. This article analyzes the resource allocation from governments and revenue generation in institutions under the reform policies of administrative decentralization and financing diversification. The new "Great Leap Forward" in higher education in 1999 and beyond, i.e., the radical and, to a certain extent, desperate mass higher education policy and practice of expanding enrollments in order to spur domestic consumption, is critically analyzed. By examining the ongoing institutional merging and "co-building" and the most recent enrollment expansion, the writer points out the economic significance for higher education of overcoming diseconomies of scale and inefficiencies. However, the long-range outcomes of the seemingly exciting investment in and consumption of mass higher education are difficult to predict.